Evaluation of immune cell infiltrates and expression of cytokines/biological molecules in the microenvironment of tumours and tumour-draining axillary lymph nodes in patients with large and locally advanced breast cancers undergoing neoadjuvant chemotherapy: crucial contribution to immune-mediated tumour cell death - Kaewkangsadan, Viriya (2016)
Background